Advanced Propulsion Systems for Unmanned Marine and ‎Subsurface Vehicles - Prabhakar , Charpe Prasanjeet; Punam, Sumit Ramswami (International Journal of Basic and Applied Sciences, 2025)
This paper goes into the latest developments in propulsion systems of Unmanned Marine and Subsurface Vehicles (UMSVs) that make a ‎significant part of maritime operations together with a military survey. The study explores ‎the conventional mechanical systems and electric propulsion, hybrid engines, and new technologies like ion drives.However, due to the complexity of underwater environments, propulsion systems must address fluid variability, pressure shifts, and multi-objective energy trade-offs. Each type of propulsion ‎is analyzed in terms of power demand, performance in varied conditions, and overall energy efficiency. Conventional mechanical systems ‎are dependable but do not excel much when it comes to energy efficiency and range of operation. The electric propulsion system, although ‎quieter and more efficient, has a battery storage usage dependency weakness that curbs its performance. Hybrid systems that integrate ‎conventional and electric propulsion modes show prowess in durability and efficiency while attempting to fill the gap between reliability and ‎energy performance. In the future, new ideas are entering the pipeline, including ion propulsion and magnetohydrodynamic technology. ‎These advanced systems attempt to minimize mechanical parts, resulting in quieter and more efficient performance. This paper addresses the ‎strengths and weaknesses of existing options for propulsion but also emphasizes cost-effective, sustainable, and modular designs that are so ‎desperately required to support the growing operational loads being imposed on UMSVs in any environment.